The Influence of Chemotherapy on the Oral Cavity Condition in Oncological Patients - a literature review - Popielarska, Kinga; Patrzykąt, Klaudia Martyna; Gorzoch-Burduk, Zofia; Brynczka, Izabela; Puzio, Julia; Marcinkowska, Paula; Krzyżaniak, Marta; Jezierski, Michal; Nowicka, Ewelina; Wróblewska, Kamila (Journal of Education, Health and Sport, 2025)
Introduction and Purpose: Chemotherapy remains one of the primary and fundamental methods of cancer treatment. It affects not only malignant cells but also the healthy tissues of the body. The side effects of oncological therapy within the oral cavity are a common and significant clinical issue, often compromising patients’ quality of life and, in some cases, hindering the continuation of treatment. The aim of this article is to review the most recent scientific literature from the past five years regarding chemotherapy- related oral symptoms in oncology patients, and to highlight the complexity of their clinical management, emphasizing the importance of a multidisciplinary approach involving specialists across various fields. Description of the State of Knowledge: Chemotherapy can induce numerous oral complications, including mucositis, ulcerations, oral pain, xerostomia, and trismus. In severe cases, some of these complications may necessitate discontinuation of cancer therapy. Xerostomia and oral microbiome alterations increase the risk of dental caries, candidiasis, and other infections. These symptoms can significantly affect the overall condition and well-being of oncology patients. Conclusions: Given the frequency ans severity of oral complications, awareness, early recognition, and appropriate preventive and therapeutic interventions are essential. Disseminating knowledge on this subject among healthcare professionals of all specialties is crucial to ensuring comprehensive, interdisciplinary care for oncology patients.